2022
DOI: 10.1155/2022/6767580
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Student Entrepreneurial Intention and the Moderating Role of Entrepreneurship Education: Evidence from an Indian University

Abstract: This study is an effort for measuring the entrepreneurial orientation of the students and its linkage with their entrepreneurial intention. The study is based on entrepreneurial dimensions such as innovativeness, need for achievements, opportunity recognition, risk-taking propensities, and entrepreneurship education. The study also used entrepreneurship education and gender as moderating variables. A 5-point Likert-type scale was designed by adapting the Individual Entrepreneurial Orientation measurement scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…The nexus between entrepreneurship orientation (in terms of innovativeness, need for achievements, opportunity recognition, risk-taking propensities and entrepreneurship education) and entrepreneurial intention has been explored. The study concluded that the entrepreneurship orientation of the students positively affects their intention to become entrepreneurs (Adhikari & Ghosh, 2023; Akhtar et al, 2022). A similar study conducted by Astiana et al (2022) showed a positive and significant association between entrepreneurship education and entrepreneurial intention.…”
Section: Review Of Literaturementioning
confidence: 98%
“…The nexus between entrepreneurship orientation (in terms of innovativeness, need for achievements, opportunity recognition, risk-taking propensities and entrepreneurship education) and entrepreneurial intention has been explored. The study concluded that the entrepreneurship orientation of the students positively affects their intention to become entrepreneurs (Adhikari & Ghosh, 2023; Akhtar et al, 2022). A similar study conducted by Astiana et al (2022) showed a positive and significant association between entrepreneurship education and entrepreneurial intention.…”
Section: Review Of Literaturementioning
confidence: 98%
“…It will further help in achieving the targets of Vision 2030 especially in increasing the share of the digital economy and making it 19.6% of the GDP of the country by 2030. A centralized virtual business incubator may further help the university in the following activities [78]:…”
Section: The Implication Of the Study And Thementioning
confidence: 99%
“…Significantly, entrepreneurship is increasingly recognized as a key driver of global economic expansion [ 2 ]. Consequently, there has been a surge in scholarly research focusing on entrepreneurial activities among various demographics, including returning migrant workers [ 3 ], researchers [ 4 ], and students [ 3 , 4 ]. Notably, students are considered central to entrepreneurial endeavors, attributed to their inherent innovative and adventurous qualities.…”
Section: Introductionmentioning
confidence: 99%